(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
In this article, a new, modern and non-standard approach, i.e. "Inclusive Diffuse" scientific theory, the methodology, mechanism and possibility of its implementation, put forward by the author in the creation of a suitable process aimed at improving the quality and efficiency of inclusive education, stabilizing the socialization and integration of students with disabilities and perspectives are highlighted